Phage-display library selection of high-affinity human single-chain antibodies to tumor-associated carbohydrate antigens sialyl Lewis(x) and Lewis(x) - Mao, Shenlan (The National Academy of Sciences, 1999)
mAbs against tumor-associated carbohydrate antigens have the potential to play a prominent role in cancer immunotherapy. However, it has not been possible to fully exploit the clinical utility of such antibodies primarily, because those of adequate affinity could be derived only from murine sources. To address this problem, we prepared a single-chain Fv (scFv) antibody library from the peripheral blood lymphocytes of 20 patients with various cancer diseases. Completely human high-affinity scFv antibodies were then selected by using synthetic sialyl Lewis(x) and Lewis(x) BSA conjugates. These human scFv antibodies were specific for sialyl Lewis(x) and Lewis(x), as demonstrated by ELISA, BIAcore, and flow cytometry binding to the cell surface of pancreatic adenocarcinoma cells. Nucleotide sequencing revealed that at least four unique scFv genes were obtained. The K(d) values ranged from 1.1 to 6.2 × 10(−7) M that were comparable to the affinities of mAbs derived from the secondary immune response. These antibodies could be valuable reagents for probing the structure and function of carbohydrate antigens and in the treatment of human tumor diseases.